Correlation between Environmental Factors and Morphological Characteristics of Koenih Rimbo (Curcuma sumatrana Miq.) as an Endangered Plant in West Sumatra - Jannah, Miftahul; Putri, Irma Leilani Eka; Kardiman, Reki; Anhar, Azwir; Putri, Dwi Hilda; Pratama, Chelsylia Dara; Valofi, Nagra Aulia; Putri, Cici Adelia; Aisyah, Siti; Djoelvinanda, Habibullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Curcuma sumatrana or Koenih Rimbo, is an endemic plant of West Sumatra that is threatened with extinction due to deforestation, climate change, and human activities. This study aims to understand the ecology of C. sumatrana to support effective conservation efforts. The study was conducted in seven potential locations in West Sumatra using exploration methods and analysis of environmental factors, such as altitude, temperature, humidity, soil pH, and canopy cover. The results showed that this species was only found in three locations, namely Lubuk Kilangan, Koto Malintang, and Koto Pulai, with the highest population in Koto Malintang. Environmental factors such as altitude, canopy cover, and air humidity were shown to support optimal growth of this species. Canonical Correspondence Analysis (CCA) identified a close relationship between environmental factors and morphological parameters, including plant height, number of branches, and leaf size. This study emphasizes the importance of natural habitat conservation and further research on the ecology of this species to prevent its extinction.